Spatial Mapping of Soil Chemical and Physical Properties in Maize (Zea mays L.) Cultivation Areas in Mootilango District, Gorontalo Regency, Indonesia - Mohune, Ramlan; Ilahude, Zulzain; S. Bagu, Fitria; Bahua, Mohamad Ikbal; Jamin, Firiah (International journal of technology and education research, 2026)
Maize (Zea mays L.) is a strategic commodity in Mootilango District; however, its productivity is still constrained by variations in soil quality. This study aimed to map the chemical and physical status of soils in maize cultivation areas in Mootilango District, Gorontalo Regency, Indonesia. A field survey and laboratory analysis were conducted using composite soil sampling from three villages, namely Pilomonu, Huyula, and Satria, representing different slope conditions. Soil chemical parameters, including organic carbon (C-organic), pH, cation exchange capacity (CEC), nitrogen (N), phosphorus (P), and potassium (K), as well as physical parameters such as soil texture, bulk density, and soil color, were analyzed. The data were spatially processed and presented using ArcGIS 10.3 to generate thematic soil maps. The results indicated that soil chemical status was generally suboptimal, characterized by low to very low levels of C-organic, N, and P, and acidic to slightly acidic soil pH (5.3–6.3), despite having high to very high CEC values. In terms of physical properties, soils were predominantly silty clay, while bulk density values in Pilomonu and Satria were relatively high (>1.70 g/cm³), indicating soil compaction. Spatial mapping identified three management zones: (1) areas with severe chemical constraints (Pilomonu: very acidic pH and low organic carbon), (2) areas with moderate chemical constraints (Satria: slightly acidic pH and low organic carbon), and (3) areas with critical organic matter limitations (Huyula: very low organic carbon with optimal bulk density). It can be concluded that improving soil fertility requires site-specific management practices, including liming, organic matter enhancement, balanced fertilization, and appropriate conservation tillage practices to support sustainable maize production.